Spatial distribution and determinants of household iodized salt utilization in Ethiopia: a spatial and multilevel analysis of Ethiopian demographic and Health survey - Yigizie Yeshaw; Adugnaw Zeleke Alem; Getayeneh Antehunegn Tesema; Achamyeleh Birhanu Teshale; Alemneh Mekuriaw Liyew; Ayenew Kassie Tesema (BMC, 2020)
Abstract Background Iodine deficiency disorder is a significant public health problem, affecting both developed and developing nations worldwide. It is associated with poor body growth and irreversible mental retardation. However, little is known about the spatial distribution and determinants of household iodized salt utilization in Ethiopia. Therefore, this study aimed to explore the spatial distribution and determinants of iodized salt utilization at national level. Methods Ethiopian Demographic and Health Survey 2016 data was used to investigate the spatial distribution and determinants of household iodized salt utilization in Ethiopia. ArcGIS 10.6 and SaTScan™ version 9.6 software were used to explore the spatial distribution and detect significant clusters, respectively. The odds ratio with its 95% confidence interval (CI) was determined for potential determinants included in the multivariable multilevel logistic regression model. Results Household iodized salt utilization was spatially clustered in Ethiopia (Moran's Index = 0.076, p-value = 0.01). The significant hotspot areas with high iodized salt utilization were located in Benishangul, Amhara, Gambella, Tigray and Northwest Oromia regions. Significant cold spot areas (areas with low iodized salt utilization) were found in Somali, and East Afar regions. Those households with higher education level ((Adjusted Odds Ratio [AOR] =1.49, 95% CI =1.14-1.93), high community level education (AOR = 1.51, 95% CI = 1.03-2.20), middle wealth index (AOR = 1.31, 95% CI = 1.04-1.65) and high community media exposure (AOR = 1.52, 95% CI = 1.07-2.17) had higher odds of iodized salt utilization. Conclusions Household iodized salt utilization had significant spatial variation across the country. Both household and community level variables were found to be associated with household iodized salt utilization in Ethiopia. Therefore, increasing the education level, wealth status and community media exposure is recommended to improve iodized salt utilization in a country. A targeted intervention is also needed for those regions with low household iodized salt utilization.